Cost stickiness and firm value - Costa MD; Habib A (Springer-Verlag GmbH, 2023)
In this paper we explore the association between cost stickiness and firm value. Using a large sample of U.S. data, we find a robust negative relationship between cost stickiness and firm value. We then explore whether the resource adjustment, managerial expectations, and agency theories of cost stickiness affect the negative relation and find support for the managerial expectation and agency theories. Furthermore, we find evidence that the detrimental impact of cost stickiness on firm value is mediated partially through the cost of equity and cash flow channels. Further investigation suggests that the adverse effects of cost stickiness on firm value is stronger in the presence of high information asymmetry. We enrich the cost management literature by integrating cost stickiness with corporate finance.
Keywords: Cost stickiness; Firm value; Agency problem; Cost of equity; Cash flow